1999
DOI: 10.1073/pnas.96.9.5274
|View full text |Cite
|
Sign up to set email alerts
|

Plaque-induced neurite abnormalities: Implications for disruption of neural networks in Alzheimer’s disease

Abstract: The brains of Alzheimer's disease patients contain extracellular A␤ amyloid deposits (senile plaques). Although genetic evidence causally links A␤ deposition to the disease, the mechanism by which A␤ disrupts cortical function is unknown. Using triple immunof luorescent confocal microscopy and three-dimensional reconstructions, we found that neuronal processes that cross through an A␤ deposit are likely to have a radically changed morphology. We modeled the electrophysiological effect of this changed morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
174
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(187 citation statements)
references
References 16 publications
9
174
0
2
Order By: Relevance
“…12I). These observations are comparable to previous findings in other AD mouse models (Knowles et al, 1999;Le et al, 2001;Tsai et al, 2004). However, until precise 3D models of these geometric distortions are produced, investigations of their functional effects (e.g.…”
Section: Quantification Of 3d Spatial Complexity In Vascular Networksupporting
confidence: 78%
See 1 more Smart Citation
“…12I). These observations are comparable to previous findings in other AD mouse models (Knowles et al, 1999;Le et al, 2001;Tsai et al, 2004). However, until precise 3D models of these geometric distortions are produced, investigations of their functional effects (e.g.…”
Section: Quantification Of 3d Spatial Complexity In Vascular Networksupporting
confidence: 78%
“…In Alzheimer's disease (AD) for example, amyloid beta protein exists in many molecular forms, and eventually aggregates into the insoluble plaques that are one of the neuropathological hallmarks of AD. Insoluble amyloid deposits comprising extracellular accumulations of amyloid beta peptide and other proteins surrounded by degenerating axons and dystrophic dendrites are an example of general histopathologic lesions that can physically distort neuronal processes in their vicinity, which must take tortuous routes around the lesions, resulting in characteristic distortions of local and global dendritic geometry (Knowles et al, 1999;Le et al, 2001;Urbanc et al, 2002). In addition, spines are often lost as spiny dendrites traverse a plaque, dendritic shafts undergo atrophy and axons in the vicinity of plaques develop varicosities (Tsai et al, 2004).…”
mentioning
confidence: 99%
“…Recent studies demonstrate that structural remodeling of synapses involving the growth of new dendritic projections may be the mechanism for long-term behavioral learning or memory (Engert and Bonhoeffer, 1999). Studies by Knowles et al (1999) suggest that amyloid-induced structural abnormalities in neuronal processes are sufficient to disturb temporal firing patterns, thereby contributing to memory loss and dementia.…”
mentioning
confidence: 99%
“…[48][49][50] However, only A␤ deposition in certain areas but not others correlates well with the degree of cognitive dysfunction. 46,[51][52][53][54][55] Furthermore, in transgenic mouse models of AD it has been shown that cognitive dysfunction may occur even before plaque deposition. 56 This and other findings have raised the possibility that soluble forms of amyloid oligomers can have an important role in initiating the disease possibly by targeting synapses.…”
Section: Imaging Structural Plasticity Of Synapses In Mouse Models Ofmentioning
confidence: 99%